If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5g + 12 = 2g + 24 Reorder the terms: 12 + 5g = 2g + 24 Reorder the terms: 12 + 5g = 24 + 2g Solving 12 + 5g = 24 + 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. 12 + 5g + -2g = 24 + 2g + -2g Combine like terms: 5g + -2g = 3g 12 + 3g = 24 + 2g + -2g Combine like terms: 2g + -2g = 0 12 + 3g = 24 + 0 12 + 3g = 24 Add '-12' to each side of the equation. 12 + -12 + 3g = 24 + -12 Combine like terms: 12 + -12 = 0 0 + 3g = 24 + -12 3g = 24 + -12 Combine like terms: 24 + -12 = 12 3g = 12 Divide each side by '3'. g = 4 Simplifying g = 4
| x^2+x-12=1 | | 8x-7=4x-5 | | 23=-3x-4x | | 23=-3x-4c | | 23=-7x | | 5n-3=2 | | 3(4+x)=5 | | x/3(x-1)-x/4(x+1)+3x+4/12=0 | | 3t+1=19 | | 5x=27-x | | 0=25-0.10q | | (8/4)+7=12 | | 8/4+7=12 | | x+6(x^2(0))=x | | ((4x+5)/(5x-8))=13/9 | | y-8+2=28 | | 4x^2+7x+5=0 | | -10p+9p=29 | | 18-12y=6y+24 | | 85=15-4x | | x^4-7x^3+48x^2i+56x+76=0 | | x^4-7x^3+48x^2+56x+76=0 | | 39-(2x+16)=2(x+4)+x | | 0=(x^2)/(0.03-x)-4.75 | | 9x+8=5X | | 2=6-32 | | 5y=22 | | 4.75=(x^2)/(0.03-x) | | 3x^2+7x+10=2x^2-5x-10 | | X+15/2=13 | | 2x+3y/2=15 | | 2x+y=6.6 |